Pengembangan Bahan Ajar Berbasis Literasi Digital dan Kompetensi Abad XXI pada Materi Barisan Kelas XI - Lutfiyah Nurul Wakhidah; Sunismi Sunismi; Alifiani Alifiani (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
The purpose of this study is to produce a product of teaching materials that are based on digital literacy and 21stcentury competence on sequence material of 11th grade. This research includes the type of research and development using the Four-D model as the basis of development that consisting of four stages, namely: (1) define, (2) design, (3) develop and disseminate. The subjects in this research and development included of one material expert, one design and learning media expert, two practiotioner validators, and 10 students of 11th grade SMAN 10 Malang as users. The types of data obtained are the scores valuation of product validation questionnaire as the quantitative data and the qualitative data from comments and suggestions on validation product questionnaire. The result f this research and development are teaching materials that are based on digital literacy and 21stcentury competence on sequence material of 11th grade which has validated by expert validators and practitioners with the purpose is to knowing the validity of the product. According to material expert, design and learning media expert, and pratitioners, teaching materials product got an average value of 4,3. Meanwhile, the result of product trials conducted on 10 students of 11th grade SMAN 10 Malang, teaching materials product got an average value 4,41. Therefore, it can be concluded that teaching materials that are based on digital literacy and 21stcentury competence on sequence material of 11th grade is valid and useable in leraning